A Multi-Unit Project for Building Scientific Confidence via Authentic Research in Identification of Environmental Bacterial Isolates - Christa Chatfield (American Society for Microbiology, 2014)
This authentic research project is designed to identify environmental isolates by metabolic phenotypes and 16s sequence analysis and with an investigation of biofilm growth is presented as implemented in an upper-level microbiology lab course. Three units were used in the lab: one for basic metabolic identification, one for the 16s rDNA sequencing and a third for biofilm growth analysis. Assessment was by weekly notebook entries detailing the outcomes of each day in lab, providing relatively on-time feedback on student understanding and learning to both the student and the instructor. The intent for these units was for each to increase the uncertainty of the project outcomes and to challenge students to design projects with open-ended results. All student groups have been able to obtain DNA sequence data in the limited 6-7 weeks of the lab project. Students report increased confidence in their abilities and a general excitement about the project methods and results. The data produced by the students can be incorporated into larger research questions posed by the faculty running the course as determined by the source of the unknown bacterial isolates.